Variation in Attitude towards Oral Healthcare Among Undergraduate Students of a Private Medical & Dental College of Karachi - Zareef, Uzma; Bakar, Imran; Khanam, Samia; Ali, Arif; Qasmi, Shamsul Arfin; Kanpurwala, Muhammad Adnan (International Journal of Pathology, 2018)
Background: Oral health is a significant attribute of general health. Dental and medical students are expected tohave good oral health care behaviors, as they are meant to evoke the same in their patients. Thus, it is necessary toassess their oral health care attitudes. The present study aims to compare the attitudes towards oral health careamong dental and medical students.Methodology: A cross sectional was conducted by utilizing HU-DBI questionnaire. Out of the total 200 studentsselected, 132 were medical and 68 were dental students of a private medical and dental collegeof Karachi selectedconveniently in the study after taking oral consent individually. The students suffering from depression or stressapparently were excluded. The statistical analysis of collected data was conducted with the help of SPSS v.17. Thedescriptive analysis was performed followed by inferential statistics.Results: The mean value for students was 19.77 ± 1.22 years with 114 (57%) females and 86 (43%) males. Asignificant difference was found between dental and medical students for oral health behaviors such as worryingabout teeth color, worrying about gums color, cleaning teeth without toothpaste, worrying about bad breath, useof dye to see teeth cleanliness, use of toothbrush with hard bristles, use of hard strokes, and taking long time tobrush teeth.Conclusion: It can be concluded on the basis of results that dental students, have better dental health practicesas compared to medical students. It is recommended that the oral health care practices should be furtheremphasized in the curriculum of both the dental and medical students from the beginning as good oral hygienehas good impact on the self confidence and overall healthcare.